2001
DOI: 10.1007/s004210100394
|View full text |Cite
|
Sign up to set email alerts
|

Are variations in running economy in humans associated with ground reaction force characteristics?

Abstract: It was hypothesized that certain ground reaction force (GRF) variables are positively correlated with running economy (RE; the aerobic demand at a single speed of running). Excessive momentum changes, quantified by linear impulse measures, as well the free moment applied to the running surface could be considered potentially wasteful efforts in terms of metabolic energy requirements. Recreational runners (n = 16) ran on a treadmill at 3.35 m.s-1 for physiological measurements and overground for biomechanical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
3
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 12 publications
7
79
3
7
Order By: Relevance
“…ADDFM for the control group in the present study was similar to that reported by Heise and Martin (2001), but IMP in the control group was lower than reported by these two groups. There are several methodological differences between each of these two studies and the present study.…”
Section: à4supporting
confidence: 89%
See 1 more Smart Citation
“…ADDFM for the control group in the present study was similar to that reported by Heise and Martin (2001), but IMP in the control group was lower than reported by these two groups. There are several methodological differences between each of these two studies and the present study.…”
Section: à4supporting
confidence: 89%
“…Gender differences in various biomechanical characteristics during running have been reported previously . Furthermore, the runners tested by Holden and Cavanagh (1991) ran at a faster speed (4.5 m s À1 ) than either of the later studies (Heise and Martin, 2001 3.35 m s À1 ; present study 3.7 m s À1 ). Speed has also been shown previously to affect the mechanics of running (Nilsson et al, 1985) and may, therefore, affect transmission of the torque to the lower extremity and the magnitude of the FM variables.…”
Section: à4mentioning
confidence: 45%
“…In the sagittal and frontal plane 56 we suggest that coordination patterns will develop which will minimise excessive changes of 57 momentum in the anterior-posterior (AP) and medio-lateral (ML) directions respectively. It is 58 likely that this strategy, suggested as a mechanism for minimising energy consumption, 59 (Heise & Martin, 2001; Williams & Cavanagh, 1987), will lead to anti-phase coordination 60 between the pelvis and thorax. This is because rotational movements of the pelvis in either 61 the sagittal or frontal planes during stance will require a rotation of the thorax in the opposite 62 direction to minimise displacement of the centre of mass (CoM).…”
mentioning
confidence: 99%
“…There are substantial inter-individual differences in running economy. Typically, variations in the order of 20-30% are reported, even among international-caliber long-distance runners (di Prampero et al, 1986;Heise and Martin, 2001;Saunders et al, 2004;Williams and Cavanagh, 1987). Previous studies on running economy have revealed that running economy is an important determinant of running performance (Anderson, 1996;di Prampero et al, 1986;Joyner, 1991;Saunders et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Second, it has been proposed that the rate and magnitude of muscular force generation explain the rate of metabolic energy consumption during running; this hypothesis is known as the 'cost of generating force' hypothesis (Kram and Taylor, 1990). Although it accounts for much of the variation in the metabolic cost of running between different animal species, it is not able to explain interindividual differences in running economy for reasons explained elsewhere (Heise and Martin, 2001). Third, it is generally accepted that storage and reutilization of elastic energy in tendons substantially reduces energy demands in running (Cavagna et al, 1964).…”
Section: Introductionmentioning
confidence: 99%